The Notions of Women’s “Economic Autonomy” and “Collective Life Project”: Conceptual Disputes and Legal Challenges in the Inter-American Human Rights System - Giudice Graña, Lucía (2025)
This article offers an analysis of the emerging notion of women’s economic autonomy within the Inter-American Human Rights System, exploring its limited but growing use in documents issued by the Inter-American Commission of Human Rights and recent judgments by the Inter-American Court of Human Rights. It argues that, although still underdeveloped in legal terms, this category holds significant potential for highlighting the material conditions that constrain the effective exercise of rights of women. Drawing on critical feminist theories of relational autonomy, the article examines how the concept of life project—increasingly employed by the Court—can serve as a gateway for a relational understanding of autonomy, particularly through the recognition of collective life projects. Through an analysis of inter-American jurisprudence and the normative discourse of institutions such as ECLAC and CEDAW, the article identifies conceptual tensions and the risk of conceptual dilution when these terms are adopted without critical scrutiny. It concludes that reclaiming and redefining the legal meaning of economic autonomy is essential to prevent its co-optation and to support a more transformative approach to substantive equality.